A catalytic protein–proteomimetic complex: using aromatic oligoamide foldamers as activators of RNase S. Issue 14 (13th March 2019) - Hegedus, Zsofia; Grison, Claire M.; Miles, Jennifer A.; Rodriguez-Marin, Silvia; Warriner, Stuart L.; Webb, Michael E.; Wilson, Andrew J.
Abstract : An aromatic oligoamide foldamer acts as an α-helix mimetic and binds to the RNase S-protein resulting in restoration of its catalytic function. Abstract : Foldamers are abiotic molecules that mimic the ability of bio-macromolecules to adopt well-defined and organised secondary, tertiary or quaternary structure. Such templates have enabled the generation of defined architectures which present structurally defined surfaces that can achieve molecular recognition of diverse and complex targets. Far less explored is whether this mimicry of nature can extend to more advanced functions of biological macromolecules such as the generation and activation of catalytic function. In this work, we adopt a novel replacement strategy whereby a segment of protein structure (the S-peptide from RNase S) is replaced by a foldamer that mimics an α-helix. The resultant prosthetic replacement forms a non-covalent complex with the S-protein leading to restoration of catalytic function, despite the absence of a key catalytic residue. Thus this functional protein–proteomimetic complex provides proof that significant segments of protein can be replaced with non-natural building blocks that may, in turn, confer advantageous properties.